Environmental law in India/edited by P. Leelakrishnan - "Leelakrishnan, P." (New Delhi, 2005)
Environmental law in India is an exhaustive study of the growth of law relating to environment in India. The third edition highlights the various aspects of environmental regime law of public nuisance and civil remedies, protection of forest habitat, natural resources and coastal zones, control of pollution, liability for environmental torts, constitutional mandate for environmental protection, judicial review of decisions affecting environment and environmental impact assessment processes. It contains a qualitative analysis of the laws pertaining to the field, reference to relevant international conventions and recent and updated case law, making it an in dispensable tool for legal practitioners, environmentalists and students of law and environment.
Keywords: Law